Pleomorphic Onychomatricoma: A Mimicker of Malignancy - Christophe Perrin; Damien Ambrosetti (Medical Journals Sweden, 2022)
Pleomorphic onychomatricoma is a rare condition mimicking malignant neoplasms. Given its rarity, the diagnostic and prognostic criteria of this condition are not well established. The aim of this study was to characterize a series of 6 cases of pleomorphic onychomatricoma. In 3 cases the submitting clinical diagnosis was subungual squamous cell carcinoma. For all 6 cases, nail clipping showed typical features of onychomatricoma as a free-edge thickening and pitting of the nail plate with an additional feature of projecting line pattern. Pleomorphic onychomatricoma was diagnosed based on moderate-severe cytological atypia, yet degenerative-appearing with multinucleation or smudged chromatin, no mitotic activity or necrosis, and a Ki67 proliferative index inferior to 5% overall. Other finding s included epithelioid multinucleated cells with deeply eosinophilic cytoplasm mimicking epithelioid malignant cells, overexpression of Ki67 and p53 on atypical cells and diffuse expression of p16. This study describes additional criteria in pleomorphic onychomatricoma, permitting a wider recognition in order to avoid inappropriate treatment.